(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the plach-koshok of Begimzhan, the daughter of Jayyl-Baatyr, in the poem “The Song of Ablay” recorded by the Kazakh scholar and traveler Ch. Valikhanov. The plach-koshok appears separately in the final part of the poem and recounts the death of her father in battle against Ablai Khan. In a historical context, it reflects an important episode of the Kyrgyz wars with Ablai Khan in the 1770s, while the plach-koshok itself serves as a valuable source for clarifying certain details of these events.